2019
DOI: 10.1017/wet.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Fluridone and acetochlor cause unacceptable injury to pumpkin

Abstract: Residual herbicides are routinely applied to control troublesome weeds in pumpkin production. Fluridone and acetochlor, Groups 12 and 15 herbicides, respectively, provide broad-spectrum PRE weed control. Field research was conducted in Virginia and New Jersey to evaluate pumpkin tolerance and weed control to PRE herbicides. Treatments consisted of fomesafen at two rates, ethalfluralin, clomazone, halosulfuron, fluridone, S-metolachlor, acetochlor emulsifiable concentrate (EC), acetochlor microencapsulated (ME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The large diversity of genetic background and seed size of cucurbitaceous crops results in a broad range of interspecific and intervarietal tolerance to soil-applied herbicides, as demonstrated by previous studies on pumpkin (Ferebee et al 2019), summer squash (Grey et al 2000b;Sosnoskie et al 2008;Trader et al 2008;Webster et al 2003), watermelon (Grey et al 2000a;Macrae et al 2008), cantaloupe (Cucumis melo L.) (Johnson and Mullinix 2005), or cucumber (Peachey et al 2012). However, the use of multiple, effective herbicide sites of action (SOAs) is one of several weed management strategies that could alleviate the rapid spread of resistance to herbicides (Norsworthy et al 2012).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The large diversity of genetic background and seed size of cucurbitaceous crops results in a broad range of interspecific and intervarietal tolerance to soil-applied herbicides, as demonstrated by previous studies on pumpkin (Ferebee et al 2019), summer squash (Grey et al 2000b;Sosnoskie et al 2008;Trader et al 2008;Webster et al 2003), watermelon (Grey et al 2000a;Macrae et al 2008), cantaloupe (Cucumis melo L.) (Johnson and Mullinix 2005), or cucumber (Peachey et al 2012). However, the use of multiple, effective herbicide sites of action (SOAs) is one of several weed management strategies that could alleviate the rapid spread of resistance to herbicides (Norsworthy et al 2012).…”
Section: Introductionmentioning
confidence: 82%
“…Squash tolerance to S-metolachlor applied PRE was also noted on pumpkin, with no more than 3% injury 4 WAP at a 0.9 kg ha −1 rate in two Virginia trials (Ferebee et al 2019). Sosnoskie et al (2008) reported an average 20% summer squash yield reduction with S-metolachlor PRE at 0.5 or 1 kg ha −1 but no effect with POST application at the same rates.…”
mentioning
confidence: 82%
“…The CS formulation is a polymer coated product that slowly releases acetochlor over time which provides longer residual weed control and improved crop safety (Cahoon et al, 2015;Fogleman et al, 2018;Li et al, 2008;Rao, 2000). However, other studies have found little to no differences among acetochlor formulations (Ferebee et al, 2019;Jursik et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Stunting, when it was observed, did not result in yield reductions under the conditions of the trials. Ferebee et al (2019) found that pumpkin treated with S-metolachlor POST directly over the tops of rows were the best yielding plots (4356 fruits/acre). Sosnoskie et al (2008) found that S-metolachlor PRE at 0.45 to 0.89 lb/acre decreased summer squash yield up to 20%, whereas POST application 3 weeks after planting (WAP) at 0.45 lb/acre did not reduce yield.…”
mentioning
confidence: 94%